A Textbook Example: Lessons Learned about Visual Content Used for an Agricultural Communications Textbook - Ricky Telg (Journal of Applied Communications, 2012)
This professional development article details lessons learned during the process of providing visual content for a new agricultural communications textbook. Textbook authors thought they had all of the visual content approved, but learned late in the textbook-writing process that many visual materials (photographs and videos) needed multiple levels of approval. Some specific “lessons learned” include being cognizant of what is in the backgrounds of visuals; knowing who owns visual content; making sure that any co-sponsor of a communications piece must approve its use, even if the lead organization approves; and receiving approval from second- and possibly third-generation visual sources. This article is important to visual communicators, in light of the move at many universities to provide content – that for many years had been provided free to clients – for a fee.
Keywords: video; photography; copyright